The effect of apoplastic pH on the nutrient uptake - Bákonyi, Nóra (Acta Agraria Debreceniensis, 2012)
The pH of soil and rhizosphare –around the roots- determine the mobility and solubility of nutrients. The exudates organic acids of plant able to modify the pH, as well as the microorganisms also take part in mobilization of nutrients. The nutrient solve mostly in mildly acidic and neutral pH. The either assumption of utilization of nutrients is the uptake by roots and of course uptake to the cells to take part in metabolism. The pH of apoplast fluid determines the solubility and uptake of nutrients to the cells. The aim of this study was to examine the effect of nutrient solution and apoplastic pH together with a bacteria based biofertiliser (Phylazonit MC®) on nutrient uptake and pH of apoplast fluid in case of nutrient solution grown plants in laboratory experiment. According to my results, the bicarbonate increased the pH of nutrient solution in due to influence the solubility and uptake of nutrients. The given bicarbonate to the nutrient solution and infiltrated into the apoplazma also modified the pH of the apoplast fluid of the test plants. The effect of bicarbonate and biofertilizer were different on the pH of the apoplast fluid and nutrient solution in nutrient solution experiment.